Penerapan Model Pembelajaran Discovery Learning Dengan Mengaitkan Ayat Al-Qur’an Untuk Meningkatkan Hasil Belajar Materi Dinamika Litosfer di Kelas X IIS MAN 1 Makassar - Yusuf, Yusuf (UNIVERSITAS NEGERI MAKASSAR, 2018)
This research is quasy experiment which aims to find out application of learning discovery learning model by linking qur'anic script to improve learning result of litosphere literature dynamics in class x iis man 1 makassar. the sample was chosen by random sampling. the research design used is Non Equivalent Pretest-Postest Control Group Design. data were collected using a multiple-choice test of 25 numbers. data analysis technique used is descriptive analysis, n-gain analysis, and inferential hypothesis tested with spss version 17.0 by using MANN-WHITNEY test with significance level 0,05. the average gain of normalized experimental classes is in the